1995
DOI: 10.1073/pnas.92.17.7824
|View full text |Cite
|
Sign up to set email alerts
|

The product of the ataxia-telangiectasia group D complementing gene, ATDC, interacts with a protein kinase C substrate and inhibitor.

Abstract: Ataxia-telangiectasia (AT) is an autosomal recessive human genetic disease characterized by immunological, neurological, and developmental defects and an increased risk of cancer. Cells from individuals with AT show sensitivity to ionizing radiation, elevated recombination, cell cycle abnormalities, and aberrant cytoskeletal organization. The molecular basis of the defect is unknown. A candidate AT gene (ATDC) was isolated on the basis of its ability to complement the ionizing radiation sensitivity of AT group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 39 publications
3
29
0
2
Order By: Relevance
“…We also found peptide sequences from histones (including histones H1.2, H2B, and H4), heat shock protein 70, ribosomal proteins (40S and 60S), and PARP1, as well as Prohibitin-2 and myristoylated alaninerich protein kinase C substrate (MARCK), which have putative roles in invasion and metastasis ( Fig. 1, Table 1) (8,(22)(23)(24). The most striking ATDC-interacting protein identified by this screen was RNF8 (37% peptide coverage by mass spectroscopy, Fig.…”
Section: Atdc Bindsmentioning
confidence: 99%
“…We also found peptide sequences from histones (including histones H1.2, H2B, and H4), heat shock protein 70, ribosomal proteins (40S and 60S), and PARP1, as well as Prohibitin-2 and myristoylated alaninerich protein kinase C substrate (MARCK), which have putative roles in invasion and metastasis ( Fig. 1, Table 1) (8,(22)(23)(24). The most striking ATDC-interacting protein identified by this screen was RNF8 (37% peptide coverage by mass spectroscopy, Fig.…”
Section: Atdc Bindsmentioning
confidence: 99%
“…Since our discovery of HINT1 by its interaction with PKC in the yeast two-hybrid system (Klein et al, 1998), other investigators have obtained evidence that HINT1 can also interact with other proteins, including the protein ATDC, which is thought to be involved in DNA repair (Brzoska et al, 1995), the protein CDK7, which plays a role in the general apparatus of transcription (Korsisaari and Makela, 2000), and MITF, a specific bHLH-zip transcription factor (Razin et al, 1999). The latter studies are of particular interest since they indicated that Ap 4 A could modulate the transcriptional activity of MITF in mast cells (Razin et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in which X-ray crystallography and in vitro enzyme assays were used to elucidate the structure and function of PKCI/HINT1, suggested that it possesses nucleotidyl hydrolase or transferase activity (Lima et al, 1997). PKCI/HINT1 has also been shown to interact with the ataxia-telangiectasia group D protein and the mi transcription factor in the yeast two-hybrid system (Brzoska et al, 1995). PKCI/HINT1 KO mice display increased susceptibility to carcinogenicity, suggesting that PKCI/HINT1 may normally play a tumor suppressor role (Su et al, 2003).…”
Section: Introductionmentioning
confidence: 99%